2014
DOI: 10.15446/abc.v19n3.42457
|View full text |Cite
|
Sign up to set email alerts
|

NESTING ECOLOGY OF THE OLIVE RIDLEY SEA TURTLE (Lepidochelys olivacea) (CHELONIIDAE) AT EL VALLE BEACH, NORTHERN PACIFIC, COLOMBIA

Abstract: The olive ridley (Lepidochelys olivacea) is the most common sea turtle to nest in Colombia. El Valle beach is considered the most important nesting beach for this species in South America. Intensive direct capture of nesting females and egg poaching for consumption and local commercial purposes has been a common practice for years. We conducted an analysis of the nesting ecology of the olive ridley on El Valle beach in the northern Pacific of Colombia in 2008. A total of 164 clutches were transferred to an art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
8
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 7 publications
4
8
0
2
Order By: Relevance
“…The overall hatching success in this study (42%) was low in comparison to that observed for olive ridley sea turtles at a solitary nesting beach (74–81%; [ 4 , 5 ]), yet comparable to previous studies at this and other mass nesting beaches [ 2 , 3 , 6 ]. However, hatching success was higher in all of our treatment plots (42%) in comparison to the area of the beach adjacent to the hatchery (nests not from this study, 27%; R. Valverde, pers.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…The overall hatching success in this study (42%) was low in comparison to that observed for olive ridley sea turtles at a solitary nesting beach (74–81%; [ 4 , 5 ]), yet comparable to previous studies at this and other mass nesting beaches [ 2 , 3 , 6 ]. However, hatching success was higher in all of our treatment plots (42%) in comparison to the area of the beach adjacent to the hatchery (nests not from this study, 27%; R. Valverde, pers.…”
Section: Discussionsupporting
confidence: 74%
“…This species of sea turtle is characterized by a nesting behavioral polymorphism, with some females nesting solitarily and others nesting in mass nesting events called arribadas [ 1 ]. Hatching success at mass nesting beaches is relatively low (0–32% vs. 74–81% at solitary beaches) and is therefore a concern for the sustainability of this natural phenomenon and the international conservation of the species [ 2 – 5 ]. Current data on the isolated effects of nest density (i.e., competition between developing embryos for respiratory gases and other resources) on hatching success suggest that nest density at arribada beaches is not high enough to single-handedly reduce hatching success to the drastically low levels observed [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The measurements of L. olivacea females found in the PNNG monitoring correspond with those reported on other beaches in the Colombian Pacific (Barrientos-Muñoz & Ramírez- Gallego, 2008;Hinestroza & Páez, 2001;Barrientos-Muñoz et al, 2014). Globally, the CCL of the nesting females of L. olivacea varies between 65.9 and 73.1 cm and those of the populations, between 60.8 and 83 cm, being the smallest marine turtle living species (Varo-Cruz, Monzón-Argüello, Carrillo, Calabuig, & Liriz-Loza, 2015).…”
Section: Discussionsupporting
confidence: 86%
“…In addition to the ETP, this species is distributed in tropical waters of the Indian and South Atlantic Ocean basins (Barrientos-Muñoz, Ramírez-Gallego, & Páez, 2015). In Colombia, it is the most common nesting turtle of the Pacific (Amorocho, Rodríguez-Zuluaga, Payán, Zapata, & Rojas, 2015), despite this, studies on its reproductive biology in Colombia have been reduced, spaced in time and carried out in a few locations (Amorocho, Rubio, & Díaz, 1992;McCormick, 1996;Martinez & Páez, 2000;Hinestroza & Páez, 2001;Pavía, Rodríguez-Zuluaga, & Amorocho, 2006;Barrientos-Muñoz & Ramírez-Gallego, 2008;Barrientos-Muñoz, Ramírez-Gallego, & Páez, 2014;Payán-Perea, Zorrilla-Arroyave, & Chirimía-Gonzáles, 2016). In this context, it is relevant to evaluate the effect that thermal variations associated with ENSO could have on marine turtle species of the Colombian Pacific, particularly on the different attributes related to the nesting process of L. olivacea in the marine protected area of Gorgona island.…”
mentioning
confidence: 99%
“…Finally, individuals of L. olivacea, with a CCL ≤59.2 cm were considered as juveniles, individuals with 59.2 ≤CCL < 64.9 cm. were considered as sub-adult and individuals with a CCL  64.9 cm were considered as adults (Barrientos-Muñoz et al, 2014).…”
Section: Study Area and Data Collectionmentioning
confidence: 99%